Comparison of Partial Indicators for Achieving SDG3 with Ecological Footprint (Journal of Universal Excellence, 2026)
Research Question (RQ): What are the interconnections between the impact of innovations as an indicator of sustainable production and sick leave as a potential partial target of SDG3 (Sustainable Development Goals) on the aggregate indicator of sustainable development (Ecological Footprint, EF)?Purpose: To indirectly demonstrate the importance of innovations for sustainable production (green transition).Method: Integral calculation of ecological footprints for the observed system (Slovenia), comparison of the calculation with technological innovation indicators and sick leave in the observed system and the EU.Results: Slovenia's innovation index in 2020 is 84.9 % and aims to reach 110 % by 2030 compared to the EU average. The ecological footprint indicator for Slovenia in 2020 is 4.78 gha, which is 102.7 % of the EU average and has been decreasing since 2008, weakly supporting the hypothesis of the environmental Kuznets curve. The index for the number of sick leave days per employee in Slovenia (2022) is 1.1 compared to the EU average, and has been rising since 2008.Organization: A healthy work environment significantly contributes to employee well-being, increased motivation, and improved physical and mental condition. As a result, sick leave is reduced, which positively affects productivity and organizational stability. Employee health is a long-term investment in the company's success. Such organizations are more resilient, innovative, and attractive to talent.Society: The 2030 Agenda for Sustainable Development was adopted at the UN Sustainable Development Summit in September 2015. It balances the three dimensions of sustainable development: economic, social, and environmental, and interweaves them across the 17 Sustainable Development Goals (SDGs). The 2030 Agenda is universal; its goals must be achieved by 2030 and must be implemented by all countries worldwide.Originality: On a theoretical level, we sought to examine the limitations of the ecological footprint method as a tool for measuring sustainable development. The method has the characteristics of integral indicators, but we found it to be most applicable in systems with well-processed statistical data. Energy flows are easier to measure than material flows. A key issue is whether the method equally captures the economic, social, and environmental aspects of sustainable development.Limitations/Future Research: Economic growth increases ecological footprints, while technological innovations contribute to reducing negative environmental impacts and achieving the SDGs. We believe that research in this area does not provide precise results due to the lack of consideration of the social environment, which we partially replace with sick leave as an indicator. Our findings highlight the importance of innovations for sustainable production and the reduction of ecological footprints.
Keywords: ecological footprint; sick leave; innovations; sustainable production; healthy work environment